Teachers' Perceptions of the Group Investigation (GI) Model for Improving Learning Outcomes and Academic Achievement in Science Instruction - Gede Yohanes Arygunartha; Victorious A Hamel; I Dewa Ayu Eka Pertiwi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to enhance learning outcomes and achievement in technology—specifically by helping students understand science and technology concepts and their real-life applications—and to foster critical thinking skills, enabling students to think critically and analytically when solving problems related to science and technology. Learning outcomes refer to changes in behavior or capabilities that occur in students following the learning process; these outcomes may manifest as acquired knowledge, attitudes, or skills. The subjects of this study are teachers at SD Negeri 3 Buduk, an educational institution implementing the *Merdeka Belajar* (Freedom to Learn) curriculum. Preliminary observations involved gathering data on student learning outcomes and achievement through interviews, observations, and documentation. The issues faced by the partner teachers included a lack of understanding regarding the Group Investigation (GI) model and concerns stemming from previous instruction on the GI model. The implementation utilized a Group Investigation (GI) approach incorporating both quantitative and qualitative methods; this involved engaging the group, selecting the venue, and designating the selected individuals as training participants. The intervention was systematically planned, with students receiving instructional materials—prepared by the team in the form of a module—covering the fundamental concepts of the Group Investigation (GI) model to improve learning outcomes.